Answer:
n= 11 & n = 13 is the answer
Answer:
5m - 4n
5(5) - 4(3) ( As m= 5 and n= 3)
25 - 12
= 13
I Can't See The Problem All The Way
Answer:
![\frac{-7x- 7}{3x + 1}](https://tex.z-dn.net/?f=%5Cfrac%7B-7x-%207%7D%7B3x%20%2B%201%7D)
Step-by-step explanation:
Given
![\frac{(x - 4)}{(2x + 1)} - 3](https://tex.z-dn.net/?f=%5Cfrac%7B%28x%20-%204%29%7D%7B%282x%20%2B%201%29%7D%20-%203)
Required
Solve
Express 3 as a fraction
![\frac{(x - 4)}{(2x + 1)} - \frac{3}{1}](https://tex.z-dn.net/?f=%5Cfrac%7B%28x%20-%204%29%7D%7B%282x%20%2B%201%29%7D%20-%20%5Cfrac%7B3%7D%7B1%7D)
Take LCM
![\frac{x - 4 - 3(2x + 1)}{3x + 1}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%20-%204%20-%203%282x%20%2B%201%29%7D%7B3x%20%2B%201%7D)
![\frac{x - 4 - 6x - 3}{3x + 1}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%20-%204%20-%206x%20-%203%7D%7B3x%20%2B%201%7D)
Collect Like Terms
![\frac{x - 6x- 4 - 3}{3x + 1}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%20-%206x-%204%20%20-%203%7D%7B3x%20%2B%201%7D)
Simplify like terms
![\frac{-7x- 7}{3x + 1}](https://tex.z-dn.net/?f=%5Cfrac%7B-7x-%207%7D%7B3x%20%2B%201%7D)
Hence:
![\frac{-7x- 7}{3x + 1}](https://tex.z-dn.net/?f=%5Cfrac%7B-7x-%207%7D%7B3x%20%2B%201%7D)
Equations : Tiger Algebra gives you not only the answers, but also the complete step by step ... 5 x 2+5 x −5=0 ... 5x^2+5x-5=0 ... Parabola, Finding the Vertex: ... Root 2 at {x,y} = { 0.62, 0.00} ...